PERAN KOMITMEN ORGANISASI SEBAGAI PREDIKTOR ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA SD SWASTA DI KOTA SERANG - Ika Pratiwi; Uli Wildan Nuryanto; Prof. Muhammad Suparmoko (Universitas Bina Bangsa, 2021)
The duties and responsibilities of a teacher in the current pandemic condition are increasingly difficult, not only carrying out daily tasks but also in developing their qualities to becomes a role models and also preparing digital teaching materials for their students. For that they needed a positive behaviour that can improve teacher performance and that behaviour is organizational citizenship behaviour (OCB)., where OCB itself influenced by other variables such as organizational commitment. For this reason, the study was developing by using 2nd order approach to analysis 248 sample from 29 private elementary school in Serang city. Organizational commitment measured by using 3 dimension and 6 indicators, while organizational citizenship behaviour measured by using 5 dimension and 15 indicators. This research using 9 hypothesis and from the result shown that all of hypothesis was accepted with the magnitude of the influence of commitment organizational on OCB is 79,1%, while the remaining 20,9% influenced by others variable outside the model tested. The affective commitment become is the dominant dimension that influencing organizational commitment, while the sportsmanship dimension is the most influential dimension for OCB. This research expected become a theoretical reference as development strategies to improve the teacher performance in the private elementary school at Serang City